PENGARUH THE LEARNING CELL TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Risdiana Chandra Dhewy; Hidayatul Innanih (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
The Learning Cell is a form of cooperative learning model. In this model one of the students has to act as a tutor. The Learning Cell can also help students understand difficult subject matter. The Learning Cell model provides opportunities for students to learn and explain to their friends according to their abilities. This study aims to determine the effect of the Learning Cell on problem solving abilities. The type of research is quantitative with a One-Shot Case Study design with a population of all class VIII students of SMP YPM 2 Sukodono, data collection was carried out during a pandemic so that the sample was only 10 students from class VIII-A using a simple random sample. Data collection techniques using observation, tests, and interviews. The purpose of observation is to assess the activities achieved by teachers and students during learning, tests are used to assess students' abilities after learning, and interviews are used to obtain research supporting data. From the results of the analysis, it is found that the assumptions are fulfilled, the residuals are normally distributed, are homogeneous, and there is no correlation between the residuals. While the partial regression obtained = 0,428 and 2,306, so (-2,306) (0,428) (2,306). Finally, H0 is accepted or there is no effect of the Learning Cell on problem solving ability.